Management of intra-vitreal cysticercosis - Yadav, SK; Winter, I; Singh, SK (Nepalese Journal of Ophthalmology, 2010)
Background: South East Asia is an endemic zone for cysticercosis. Oocular cysticercosis is emerging as a common problem which if untreated can lead to severe visual loss in 3-5 years. Cases: We describe here a case series of three patients with intravitreal cysticercosis and managed by surgical cyst removal by pars plana vitrectomy. Observation: The procedure was successful in all cases to maintain anatomical integrity of the globe with some functional gain of vision. Conclusion: Surgical intervention in ocular intravitreal cysticercosis is an acceptable approach with good results. Key words: cysticercosis; ocular cysticercosis; intravitreal cysticercosis DOI: 10.3126/nepjoph.v1i2.3692 Nep J Oph 2009;1(2):143-145